HMMCCN: a hierarchical mobility management scheme for content-centric networking. (2016) - Ren, Fei; Zhou, Huachun; Yi, Li; Qin, Yajuan; Zhang, Hongke
Content-centric networking (CCN) has emerged as a promising paradigm in current internet. Owing to the interest-driven, we concern more about the content itself rather than the place it located, and therefore, CCN supports subscriber mobility natively, however, it remains a major challenge in publisher mobility. In this paper, we propose a hierarchical mobility management scheme for CCN (HMMCCN) which contains an overlay mapping structure to store the old-to-new name binding relationship and perform the mobility management for mobile devices. This allows for efficient simultaneous mobility and supports seamless handoff for interactive communication. The main goals of this paper are: a) to propose a mobility scheme suitable for all mobile nodes in CCN, both the publishers and subscribers; b) to describe the hierarchical mobility management procedure during intra-domain and inter-domain handoff; c) to establish an analytical model and formulate the location update signalling cost, handoff delay; d) to calculate kopt in the content router (CR) for decreasing the total overhead during handoff.